Spider prey-wrapping silk is an α-helical coiled-coil/β-sheet hybrid nanofiber12. Issue 76 (7th September 2018) - Addison, B.; Onofrei, D.; Stengel, D.; Blass, B.; Brenneman, B.; Ayon, J.; Holland, G. P.
Abstract : Solid-State NMR results on 13 C-Ala/Ser and 13 C-Val enriched Argiope argentata prey-wrapping silk show that native, freshly spun aciniform silk nanofibers are dominated by α-helical (∼50% total) and random-coil (∼35% total) secondary structures, with minor β-sheet nanocrystalline domains (∼15% total). Abstract : Solid-State NMR results on 13 C-Ala/Ser and 13 C-Val enriched Argiope argentata prey-wrapping silk show that native, freshly spun aciniform silk nanofibers are dominated by α-helical (∼50% total) and random-coil (∼35% total) secondary structures, with minor β-sheet nanocrystalline domains (∼15% total). This is the most in-depth study to date characterizing the protein structural conformation of the toughest natural biopolymer: aciniform prey-wrapping silks.